Large-area fabrication of ultrathin metal-organic framework membranes - Yuan, Hongye (2024)
Metal-organic framework (MOF)-based membranes, featuring potential molecular sieving effects and therefore capable of surmounting the ubiquitous trade-off between membrane selectivity and permeability, hold great promise for multitudinous chemical separations. Nevertheless, it remains highly challenging for the large-area fabrication of ultrathin MOF membranes with variable thickness, great homogeneity, and preferential orientation. Herein, this work reports the facile fabrication of ultrathin (down to 20 nm) NUS-8 membranes in large-area (>200 cm2 ) yet with great homogeneity and texture along (00l) direction due to the superior solution processability of the as-synthesized NUS-8 nanosheets. The resultant NUS-8 membranes with good adhesion properties and certain flexibility exhibit excellent rejections (>98% for Mg2+ and Al3+ , and dyes with molecular weights larger than 585.5 g mol-1 ) toward aqueous separation of various metal ions and dyes at modest permeance (1-3.2 L m-2 h-1 bar-1 ) due to the well-aligned structures. Such separation performance outstands among polymetric membranes, thin-film composite membranes, mixed matrix membranes, and other MOF membranes reported in the literature. The separation mechanism is reasonably discussed based on the experimental and theoretical results. This study opens up novel perspectives for preparing ultrathin and large-area MOF membranes using the solution processability of MOFs.